In Silico Study of the potency of Drynaria rigidula (Sw.) Bedd. (Polypodiaceae) compounds in breast cancer therapy targeting AKT1 protein pathways - Naufal Ma'arif; Sefti Adelia; Alifia Dwinanti Hakamashe; Fadila Nur’anfa Putri; Nailul Rahmi Aulya; Supriyatin (Bioma, 2024)
Breast cancer is the second most prevalent cancer globally. One of the key pathways involved in breast cancer is the PI3K/Akt mechanism. A natural compound with potential that has not been extensively studied is Drynaria rigidula (Sw.) Bedd., a Polypodiaceous fern native to Indonesia and is commonly used in traditional medicine. This study aims to explore the potential of Drynaria rigidula as an anti-breast cancer agent. The method used in silico analysis by collecting data from several web servers such as SwissADME (https://www.swissadme.ch/) with the parameters Lipinski’s rule of five, Veber, Egan, and Way2Drug for biological activity. The protein used in this study is AKT1 (PDB ID: 6HHF), obtained from the RCSB database. Molecular docking analysis was conducted using PyRx software with visualization performed in Biovia Discovery Studio. The results showed that several compounds, such as 3,4-dihydroxybenzoic acid, fern-9(11) ene, Stigmasterol, dan Campesterol, had RMSD values < 3.0 Å and binding affinities of -9.4, -9.2, -7.6, and -7.6 respectively. These results were compared with the control ligand AZD5363 and doxorubicin, which had a binding affinity from each other are -8.3 and -7.4. Therefore, the docking results indicate that compounds from Drynaria rigidula are predicted to have potential as anti-cancer agents.